Social networks scopophilic dimension: social belonging through spectatorship - Mateus, Samuel (2012)
As images become more and more omnipresent our relation to them assumes new contours. Contemporary social networks place a singular emphasis in the optic apparatus challenging traditional networked media studies to take into account new objects and social processes. This paper aims to bring contributions from visual culture studies into the research about social networks audiences and the relations they establish with the medium and with its users. It will argue that scopophilia may be a dear concept to evaluate how people socially interact in social networks. This scopophilic dimension transforms users into spectators. Spectatorship would be, then, a fundamental notion, not only to understand the social role of pictures and videos on social networks as also to understand how social networks contribute to the promotion of social organization and cohesion. The paper will discuss how scopophilia and spectatorship lead to the formation of communities of vision and the redefinition of intimacy in contemporary societies.